Recombinant dimeric envelope vaccine against flaviviral infection - Peters, Iain; Coller, Beth-Ann; McDonell, Michael; Ivy, John; Harada, Kent (2003)
The present invention discloses and claims vaccines containing, as an active ingredient, a secreted recombinantly produced dimeric form of truncated flaviviral envelope protein. The vaccines are capable of eliciting the production of neutralizing antibodies against flaviviruses. The dimeric forms of truncated flaviviral envelope protein are formed 1) by directly linking two tandem copies of 80% E in a head to tail fashion via a flexible tether; 2) via the formation of a leucine zipper domain through the homodimeric association of two leucine zipper helices each fused to the carboxy terminus of an 80% E molecule; or 3) via the formation of a non-covalently associated four-helix bundle domain formed upon association of two helix-turn-helix moieties each attached to the carboxy terminus of an 80% E molecule. All products are expressed as a polyprotein including prM and the modified 80% E products are secreted from Drosophila melanogaster Schneider 2 cells using the human tissue plasminogen activator secretion signal sequence (tPA L ). Secreted products are generally more easily purified than those expressed intracellularly, facilitating vaccine production. One embodiment of the present invention is directed to a vaccine for protection of a subject against infection by dengue virus. The vaccine contains, as active ingredient, the dimeric form of truncated envelope protein of a dengue virus serotype. The dimeric truncated E is secreted as a recombinantly produced protein from eucaryotic cells. The vaccine may further contain portions of additional dengue virus serotype dimeric E proteins similarly produced. Another embodiment of the present invention is directed to methods to utilize the dimeric form of truncated dengue envelope protein for diagnosis of infection in individuals at risk for the disease. The diagnostic contains, as active ingredient, the dimeric form of truncated envelope protein of a dengue virus serotype. The dimeric truncated E is secreted as a recombinantly produced protein from eucaryotic cells. The diagnostic may further contain portions of additional dengue virus serotype dimeric E proteins similarly produced.